Letter - Roberts, Wilfrid
037-0082-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF CHAIRMAN: THE DUCHESS OF ATHOLL, M.P. VICE-CHAIRMEN: THE EARL OF LISTOWEL MISS ELEANOR RATHBONE, M.P. HON. SECRETARIES: MR. D.R. GRENFELL, M.P. CAPT. J.R.J. MACNAMARA, M.P. MR. WILFRID ROBERTS, M.P. HON. TREASURER: MR. WILFRID ROBERTS, M.P. ORGANISING SECRETARY: MRS. MARY M. MILLER 53, MARSHAM STREET, LONDON, S.W.1 TELEPHONE: VICTORIA 2168 16th July, 1937. Dear Mr. Tewson, I understand that you have already received a receipt for £10, but I would like to add a letter to thank you personally for your very kind gift, which I know was much appreciated by the children. Yours sincerely, Wilfrid Roberts H.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/37/82